Eastern Caribbean Currency Union : 2010 Discussion on Common Policies of Members Countries-Staff Report; Informational Annex, and the Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
Real regional gross domestic product (GDP) contracted by 6 percent in 2009, reflecting a collapse in tourist arrivals and foreign direct investment (FDI)-financed construction activity. The global financial and economic crisis has also exposed areas of significant weaknesses, notwithstanding reforms implemented by a number of member countries. Executive Directors concurred that the urgent challenge is fiscal consolidation. They noted IMF staff's assessment that the real effective exchange rate (REER) appears broadly in line with current fundamentals.